REGULATION OF HUMAN INTESTINAL ORGANOID REACTIVE OXYGEN SPECIES PRODUCTION AND MITOCHONDRIAL FUNCTION BY DUOX2 GENETIC VARIATION AND MICROBIAL PRODUCTS. (21st January 2021) - Jurickova, Ingrid; Novak, Elizabeth; Angerman, Elizabeth; Bonkowski, Erin; Mollen, Kevin; Denson, Lee
Abstract: Introduction: The DUOX2 intestinal epithelial NADPH oxidase is upregulated in Crohn's Disease (CD), and DUOX2 mutations are associated with increased CD risk. Oxidative stress and loss of mitochondrial function disrupt the intestinal barrier promoting inflammatory responses to commensals. The relative impact of DUOX2 mutations and microbial products in this regard is poorly understood. Hypothesis: We hypothesized that DUOX2 genetic variation would be associated with differences in cellular reactive oxygen species (ROS) production and mitochondrial function in a Human Intestinal Organoid (HIO) model system. Methods: Induced pluripotent stem cell lines derived from pediatric CD patients with and without combined DUOX2 missense mutations(R701Q, P982A, and H678R) were used to generate wild type (WT) and DUOX2 mut HIOs. Reactive oxygen species (ROS) production was measured using the two-color ROS-ID® Total ROS/Superoxide detection kit, and the mitochondrial membrane potential (MMP) was measured using JC1 staining by flow cytometry in HIO EpCAM+ epithelial cells and CD90+ stromal cells. Expression of inflammatory and mitochondrial genes which varied with DUOX2 mutation carriage in CD patent ileal biopsies was measured by RT-PCR. HIO mitochondrial complex I and II activity was measured using an Oroboros respirometer. Results: Epithelial ROS production was reduced in DUOX2 mut HIO under basal conditions; this difference was not observed following pyocyanin stimulation (Fig. 1A). A profound suppression of epithelial ROS production was observed following butyrate treatment. Butyrate did not alter stromal cell ROS production. Under these conditions, induction of ROS by pyocyanin was abrogated in WT, but not DUOX2 mut HIO epithelial cells (Fig. 1B). Butyrate increased expression of core genes regulating the mitochondrial respiratory chain and DNA synthesis ( COX5B, NDUFA1, POLG2, SLC25A27 ) and HIF1A implicated in barrier function, independent of genotype (p<0.05). The epithelial and stromal cell mitochondrial membrane potential (MMP) (Fig. 2A), and HIO mitochondrial complex I activity (Fig. 2B), were reduced in DUOX2 mut HIO under basal conditions. This was specific, as mitochondrial complex II activity did not vary with DUOX2 genotype. Conclusions: We confirmed epithelial effects of DUOX2 genotype and butyrate exposure on ROS production in the HIO model system. Genotype dependent effects on basal ROS production were largely abrogated by the microbial products pyocyanin and butyrate, although butyrate inhibition of pyocyanin induced ROS production was dependent on intact DUOX2 function. Data suggest a previously unanticipated effect of DUOX2 genetic variation on the epithelial and stromal cell MMP and cellular respiration. This may have implications for mechanisms by which DUOX2 regulates barrier function and inflammatory responses to commensals in CD.